Cardiac magnetic resonance follow-up of COVID-19 vaccine associated acute myocarditis - Kravchenko, Dmitrij; Isaak, Alexander; Mesropyan, Narine; Bischoff, Leon M.; Pieper, Claus C.; Attenberger, Ulrike; Kuetting, Daniel; Zimmer, Sebastian; Hart, Christopher; Luetkens, Julian A. (Frontiers in Cardiovascular Medicine, 2022)
Background Mass COVID-19 vaccination campaigns have helped impede the COVID-19 pandemic. In rare cases, some vaccines have led to vaccine associated myocarditis in a specific subset of the population, usually young males. Cardiac magnetic resonance (CMR) can reliably diagnose vaccine associated myocarditis, but follow-up data of CMR proven acute myocarditis is scarce. Materials and methods Nine patients with acute vaccine associated myocarditis underwent baseline and follow-up CMR examinations and were compared to baseline parameters at initial presentation and to a group of 20 healthy controls. CMR protocol included functional assessment, T1 and T2 mapping, T2 signal intensity ratio, strain feature tracking, and late gadolinium enhancement (LGE). Results Myocarditis patients (n = 9, aged 24 ± 6 years, 8 males) underwent CMR follow-up after an average of 5.8 ± 4.3 months. All patients showed a complete resolution of visual myocardial edema while also demonstrating a reduction in overall LGE extent from baseline to follow-up (4.2 ± 2.1 vs. 0.9 ± 0.8%, p < 0.001), although visual LGE was still noted in all patients. Left ventricular ejection fraction was normal at baseline and at follow-up (58 ± 6 vs. 62 ± 4%, p = 0.10) as well as compared to a healthy control group (60 ± 4%, p = 0.24). T1 (1024 ± 77 vs. 971 ± 34 ms, p = 0.05) and T2 relaxations times (57 ± 6 vs. 51 ± 3 ms, p = 0.03) normalized at follow-up. Most patients reported a resolution of clinical symptoms, while two (22%) reported new onset of exertional dyspnea. Conclusion Patients with COVID-19 vaccine associated acute myocarditis showed a complete, uncomplicated resolution of myocardial inflammation on follow-up CMR, which was associated with a near complete resolution of symptoms. Minor, residual myocardial scarring was present on follow-up LGE imaging. The long-term implications of the remaining myocardial scar-tissue after vaccine associated myocarditis remain unknown warranting further studies.